(untitled) (Journal of Energy and Safety Technology (JEST), 2021)
The importance in identifying safety critical task in high-risk industries for competence assessment is greatly emphasised to ensure the personnel is well equipped with high level of competence and assurance in certain safety critical tasks. Lack of competency had resulted in various accidents in oil and gas industry. Failure in escape, evacuation, and rescue (EER) operation in history has led to tragic consequences associated with high number of fatalities, such as Alexander L. Kielland platform collapse, Piper Alpha disaster and tragedy of Ocean Ranger. Although competency assessment is widely implemented in offshore industry, accident still occur which indicates that reliable competency assessment is highly essential. In this research, a technical competency assessment tool is developed to assess the technical skills of each individual in emergency response team during EER activities. Case studies are selected to evaluate the designed Emergency Response Team Technical Competency (ER2TC) assessment tool where a range of different inputs and parameters are designed and tested on the designed tool. Analysis is conducted to identify how the overall output is affected by the uncertainty from the designed tool’s input and discover the impact of potential errors in the tool towards the output generated from the tool. The ER2TC assessment tool overcomes personal subjectivity and biasness of assessors, thus, producing reusable and reliable tool for decision makers in the evaluation of candidates. This tool has also implemented stricter assessing criteria to evaluate the performance of candidates in EER activities. This is seen as necessary due to the critical nature and the must to ensure the successful for EER operations as any failure could potentially results in loss of lives. Thus, this ER2TC assessment tool has indeed sufficient to assess the technical skills of personnel in ensuring the success of EER operations in offshore installations.